The COVID‐19 social media infodemic (2020)
We address the difusion of information about the COVID-19 with a massive data analysis on Twitter, Instagram, YouTube, Reddit and Gab. We analyze engagement and interest in the COVID-19 topic and provide a diferential assessment on the evolution of the discourse on a global scale for each platform and their users. We ft information spreading with epidemic models characterizing the basic reproduction number R0 for each social media platform. Moreover, we identify information spreading from questionable sources, fnding diferent volumes of misinformation in each platform. However, information from both reliable and questionable sources do not present diferent spreading patterns. Finally, we provide platform-dependent numerical estimates of rumors’ amplifcation.